Primordial Symptoms and ECG Among Sudden Cardiac Death Victims Due to Primary Myocardial Fibrosis - Silvola, H.; Pakanen, L.; Holmström, L.; Perkiömäki, J. S.; Eskuri, M. A. E; Huikuri, H. V.; Junttila, M. J. (Clinical cardiology (Mahwah, N.J.), 2025)
ABSTRACT Background Sudden cardiac death (SCD) remains a major cause of death despite progress in prevention and intervention of cardiac diseases. The most common cause of nonischemic SCD in young individuals in Northern Finland is primary myocardial fibrosis (PMF). Methods Fingesture study consists of 5869 prospectively collected subjects with SCD from Northern Finland collected from 1998 to 2017. Nonischemic etiology was the cause of SCD in 1477 (25%) subjects out of which primary myocardial fibrosis was the cause of SCD in 184 (12%) subjects (65% men, median age 55 ± 16 years). We examined the ante mortem ECG and medical history of the subjects to discover preceding symptoms and ECG changes. Results Prior health care contact in electronic health record system (EHR) was found for 89 (48%) subjects and ECG was available for 52 (28%) subjects. Both medical history and ECG were available for 20 subjects (11%). We observed that transient loss of consciousness (TLOC) was the most common symptom recorded and was reported by 33 (37%) subjects. ECG was abnormal in 38 (73%) subjects. Fragmented QRS (fQRS) complex was found in 26 (50%) subjects. Vast majority, 87% of subjects had either TLOC or abnormal ECG. Only seven subjects with ECG or EHR history available had normal ECG and did not have TLOC. Conclusions Many SCD victims with primary myocardial fibrosis had abnormal ECG or history of TLOC. The results suggest that the combination should generate careful cardiovascular examination to detect underlying myocardial disease and possibly prevent SCD. Patients with primary myocardial fibrosis (PMF) may be present with abnormal ECG and/or transient loss of consciousness. Especially the combination of the two should indicate the need for further medical examination.